Will China s Development lead to Mexico s Underdevelopment? - Schwartzman, Kathleen C. (Región y Sociedad., 2018)
China has become an important global actor in the arenas of production, trade, and foreign investment. In 1948, China contributed slightly less than 1 percent to global exports; by 2013, it had grown to almost 12 percent. Has China's vertiginous trade growth come at the expense of other exporters or does it represent an expansion of new consumer markets? For policy makers in the so-called "emerging markets," this is most relevant since many have adopted the export-led model as their engine of development. The goal of this article is to add to the current literature on the effect of China's growth on Mexico. Combining elements of world-systems, race-to-the-bottom, and global commodity chain frameworks, I analyze the consequences of China's export growth in garlic. The evidence strongly suggests that China's entrance into this global market has had deleterious consequences for Mexico's production and exports.